A study on air levitation aspects on an air - cushion vehicle - Chia, Joanna Wen Ni (2015)
‘Partial Air Levitation Trains’ is a method that will be introduced in this report. Concepts involving air levitation is incorporated to improve the current train system. However, unlike air levitated trains, it will not be lifted from the ground and still require train wheels for forward movement. Instead, the upward force created by air is used to ease the load of train and reduce the weight placed on the train wheels. An air cushion is formed by enclosing the area between the train carriage base and the tracks with metal plates. However, for smooth movement of the train, a small gap will definitely exist between the metal plates and the track which will result in air leaking from the gap. To maintain the same lifting force, the same volume of air needs to be maintained in the enclosed area. To achieve that, air has to constantly be supplied into the enclosed area to replenish the leaked air. Thus, knowledge about the air leakage is crucial and essential for determining the feasibility of idea. Acquiring information and other data about the amount of air needed for replenishing the leakage would be the main purpose of this report. The study topic would be to find out the influence of pressure difference and gap dimensions have on the leakage volume flowrate of air. The determining of volume flowrate of air leakage is achieved by two approaches. The first approach is done using theoretical calculation. Two separate core relations, namely power law and quadratic law, were obtained from two different sources. Results obtained from this two core relations have close results which inferred that the two relations found were reliable. The second approach was carried out to further verify the two core relations. A more comprehensive two dimensional flow approach based on commercially available CFD computational code, Ansys Fluent was used. Using this CFD code, results on leakage flowrate of air for various operating parameters including pressure differences and gap sizes were obtained and analyzed. The results showed that values obtained from the two core relations mentioned earlier were in good agreement with those from CFD code. However, the results obtained from power law have a higher degree of closeness to the computational results as compared to the results obtained from quadratic law. This leads to a conclusion that power law is a better prediction model for leakage volume flowrate of air. Further calculations using the values of volume flowrate were done. The diameter of compressor required and cost of supplying the air to replenish the leakage was found. The values were practical, supporting the feasibility of ‘Partial Air Levitation Train’.